2015
DOI: 10.1177/1355819615593302
|View full text |Cite
|
Sign up to set email alerts
|

Why does increasing public access to medicines differ between countries? Qualitative comparison of nine countries

Abstract: Different factors limit or enable reclassification, affecting consumer access to medicines in different countries. For countries attempting to reduce barriers to reclassification, solutions may include garnering government support for reclassification, support and flexibility from the medicines regulator, having a pharmacy-only and/or pharmacist-only category, providing market exclusivity, ensuring best practice in pharmacy, and minimizing the cost and delays of reclassification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 14 publications
2
50
1
2
Order By: Relevance
“…The main barrier to reclassification perceived by respondents was opposition from other health professional bodies, which was consistent with pilot interviews and previous Australian research that identified ‘patch protection’ as a barrier to Australian reclassification . This may be influenced by a perceived loss of income as Australian medical practitioners are paid on a fee for service model .…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The main barrier to reclassification perceived by respondents was opposition from other health professional bodies, which was consistent with pilot interviews and previous Australian research that identified ‘patch protection’ as a barrier to Australian reclassification . This may be influenced by a perceived loss of income as Australian medical practitioners are paid on a fee for service model .…”
Section: Discussionsupporting
confidence: 79%
“…The World Self‐Medication Industry strongly supports international policy change that improves opportunities for self‐care to contribute to improved health outcomes and more sustainable healthcare systems . Perhaps it is time to consider more creative approaches to policy change with regards to medicines reclassification . One creative approach to policy changes is exemplified by New Zealand, where non‐sponsor stakeholders, such as pharmacy retail groups, were proactively involved in reclassification applications within models that balanced increased access with safety controls .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations